Holding the door slightly open: Germany's migrants' return intentions and realizations - Hend Sallam (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
Return migration intentions are complex and are not necessarily followed by future return migration. Our study compares successful return or repeated migration with self-declared return intentions. We take advantage of the latest German Socio-Economic Panel survey dropout studies and fieldwork to observe a wider return migration window than reported in the literature to answer the question of whether return migration intentions eventually coincided with actual emigration behaviors. We also examine the validity of return migration estimates. This paper explores whether return intentions eventually materialize, whether they can eventually predict actual return behaviors, and if the determinants of actual and predicted return based on intentions are similar. Overall, our results support that migration intentions can predict actual return behavior. While our results show discrepancies in the predictors of return intentions and actual returns, they show emigration intentions as good predictors of actual future emigration. Moreover, we find that life satisfaction significantly impacts the individual intention to remigrate.
Keywords: F22; J61; I31; 330; return and repeat migration; emigration; self-selection; intentions and realizations; West Germany